Differences in the neural mechanisms of selective attention in children from different socioeconomic backgrounds: an event-related brain potential study - Stevens, Courtney; Lauinger, Brittni; Neville, Helen (Developmental Science, 2009)
Previous research indicates that children from lower socioeconomic backgrounds show deficits in aspects of attention, including a reduced ability to filter irrelevant information and to suppress prepotent responses. However, less is known about the neural mechanisms of group differences in attention, which could reveal the stages of processing at which attention deficits arise. The present study examined this question using an event-related brain potential (ERP) measure of selective auditory attention. Thirty-two children aged from 3 to 8 years participated in the study. Children were cued to attend selectively to one of two simultaneously presented narrative stories. The stories differed in location (left/right speaker), narration voice (male/female), and content. ERPs were recorded to linguistic and non-linguistic probe stimuli embedded in the attended and unattended stories. Children whose mothers had lower levels of educational attainment (no college experience) showed reduced effects of selective attention on neural processing relative to children whose mothers had higher levels of educational attainment (at least some college). These differences occurred by 100 milliseconds after probe onset. Furthermore, the differences were related specifically to a reduced ability to filter irrelevant information (i.e. to suppress the response to sounds in the unattended channel) among children whose mothers had lower levels of education. These data provide direct evidence for differences in the earliest stages of processing within neural systems mediating selective attention in children from different socioeconomic backgrounds. Results are discussed in the context of intervention programs aimed at improving attention and self-regulation abilities in children at-risk for school failure.
Keywords: petite enfance; préscolarisation